Petroleum Fiscal Regimes Attractiveness in Indonesia, Malaysia and Thailand: Application on Offshore Project Development - Dwi Atty Mardiana; Pri Agung Rakhmanto; Shabrina Sri Riswati; Eleonora Sofilda; Saptianta Aribawa; Gabriela Martines (Testing Center for Oil and Gas LEMIGAS, 2024)
Several factors are required to be considered in offshore and deepwater field development, including uncertainty in geological conditions, advanced technology, investment needed, fluctuating oil and gas prices, as well as fiscal regimes. Therefore, this study aimed to compare and evaluate the economic and fiscal regimes attractiveness ranks in Indonesia, Malaysia, and Thailand, applied to three cases of offshore oil and gas field development. The three offshore field cases included a new frontier gas field (Block A), a developed deep-water gas field (Block B), as well as a mature oil and gas field (Block C) with reserves of more than 100 mmboe and an investment range of 3 to 9 billion dollars. The discounted cash flow model was used to evaluate the contractor profitability, while government take, front loading index (FLI), and composite score (CS) were applied to rank the fiscal regime attractiveness. The result showed that profit split and ceiling of cost recovery affected fiscal attractiveness in government take. Front loading for contractor was observed at the early production phase from royalty and profit split. The fiscal attractiveness ranking generated a different order for each case, with Indonesia PSC CR being the most attractive to use in Block A due to the lowest FLI value. This PSC GS was the most attractive to use in Block B, providing the best economic results. Furthermore, concession scheme in Thailand was the most attractive to use in Block C, showing the best economic and the lowest FLI value. This showed that regardless of fiscal regime used in a country, parameter flexibility should accommodate uncertain conditions